Validity and Reliability of Higher Order Thinking Skills (HOTS) Test Assessment in Mathematics Learning At Seventh Grade Based on The Expert Study - subay, Resvia; Kartono, Kartono; Sulhadi, Sulhadi (Journal of Research and Educational Research Evaluation, 2019)
This paper is a part of research and development that develops Higher Order Thinking Skill test assessment in mathematics learning in seventh grade. The developed test assessment is in the form of essay questions, consisting of 10 question items. In a research and development study, one of the required steps before conducting a trial run test is an expert study. The expert study is carried out to find out the validity and reliability of a developed instrument based on experts' judgment. The developed test assessment in this research is based on three experts' judgments. They are a mathematician, an evaluation expert, and a practitioner (mathematics teacher). Then, the scores taken from the expert study were then analyzed by using the Aiken formula. Meanwhile, the reliability was analyzed by using Ebel. The validity score of 10 question items shows each of them has a validity score toward three aspects. The aspects are content, construct, and language. The aspects consist of 14 principles. Meanwhile, the reliability test has a score . Thus, the developed test assessment, based on the expert study, is valid and reliable.